United States Food and Drug Administration’s Accelerated Approval Pathway: Progressive Journey and Opportunities for a Balancing Act for Oncology Drugs - Vats, Rajneesh (Global journal of Business and Integral Security, 2025)
Accelerated Approval Pathway is one of the most sought-after approval approaches of USFDA for Oncology Drugs. It has been criticized for some of its shortcomings that may leave a void to expose Cancer patients to not so better perceived safe, efficacious and quality drugs. Out of various challenges associated with it, challenges associated with timeboxing of confirmatory clinical studies; incentivization opportunities or exercising penalization of Sponsors for diligently conducting or not conducting the confirmatory clinical studies, respectively; introduction of drug product label modifications for drug products which have received accelerated approvals; and striking checks and balances on the costs of drug products approved through this approval pathway were chosen to be studied as part of this research work. This work involved quantitative & qualitative methods on the responses received to questionnaires containing close-ended and openended questions on topics of highlighted challenges from relevant professionals from R&D, Regulatory Affairs, Clinical Healthcare & Key Opinion Leaders (KOLs) and pharmaceutical academics, primarily. Efforts were also made to reach out to Health Authority stakeholders and seek their viewpoints on these issues; however, no response was received from their side. A total of 57 participants responded to the questionnaires and out of them 51 were legitimate respondents. On responses to close-ended questions, analysis was done with the help of application of statistical techniques, like, mean, median, mode and standard deviation. Also, Chi-square analysis and Cramers’ V analysis were performed to see the association of variables and strength of association of variables, respectively. On responses to open-ended questions, analysis was done with the help and Natural Language Processing (NLP) techniques comprising of Topic Modeling (LDA). From the analysis, it can be understood that timeboxing holds the key in good conductance of clinical trials and prove be an important torchbearer for early patient access of drugs with utmost safety, efficacy and quality profiles. Similarly, both incentives and penalties play a crucial role in ensuring that sponsors conduct their clinical trials on time. By offering prioritization in review processes, market exclusivity, and public recognition, sponsors are motivated to complete their trials efficiently. On the other hand, financial penalties, FDA involvement, and the withdrawal of approvals serve as strong deterrents for sponsors who fail to meet their obligations. For label modifications, the responses are indicative of a positive perception of modifications proposed on the labels/ prescribing informations. The suggestions provided by respondents reflect a deep concern for safety, transparency, and effectiveness when it comes to drug labeling. Costs of drug products always hold the key in better patient access. This analysis reveals that respondents identified a wide range of variables and measures that could help regulate drug prices.